PENDAMPINGAN MIGRASI APLIKASI AKUNTANSI UNTUK USAHA TAMBAK DI MUNGGANGSARI PURWOREJO: DARI APLIKASI BUKU KAS KE CATATAN KEUANGAN - Agung Praptapa (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
Heathy business needs good financial record. Businesspeople use many ways to record their financial transaction. Free bookkeeping applications are commonly use in business, especially in small busines. Initially, application of Buku Kas is commonly used. However, on May 26, 2023 application of Buku Kas was officially closed. Alternatively, some people use application of Catatan Keuangan to record their business financial transaction. Team of Public Service in Faculty of Economics UNSOED train the shrimp pond businesspeople in Purworejo to migrate from Buku Kas Application to Catatan Keuangan Application.